Climatology of heavy precipitation over Corsica in the period 1985–2015. (27th December 2017) - Scheffknecht, P.; Richard, E.; Lambert, D.
Abstract : The island of Corsica in the western Mediterranean is frequently struck by devastating heavy precipitation events (HPEs), which endanger property and lives alike. In the framework of the Hydrological Cycle in the Mediterranean Experiment (HyMeX) project, multiple HPEs from 2012 were observed and studied, and to provide context, a climatology for HPEs based on 31 years (1985–2015) of surface observations was derived, based on 173 events. HPEs (>100 mm day −1 ) strike the island around 5–6 times a year and show a distinct seasonal cycle. They occur predominantly during autumn, with more than half of the HPEs occurring from September to December and almost 20% in October, the most active month. The eastern half of the island is most affected by HPEs. Composite fields for all events show a cyclone over the western Mediterranean west of Corsica, and warm and moist low‐level air upstream of the orography, predominantly over the Tyrrhenian Sea southeast of the island. The events are classified using their synoptic and mesoscale environment obtained from ERA‐Interim data. Using empirical orthogonal functions (EOFs) and a principal component (PC) analysis together with the k ‐means clustering algorithm, three clusters of events are identified. Each has a different seasonal cycle, dominant wind direction, and precipitation distribution. Warm southeasterly events occur predominantly in autumn, produce the most extreme events and affect the coasts and slopes of eastern Corsica alike. Cool southeasterly events occur predominantly in winter and affect mostly the slopes along the east side of the orography. Southwesterly events are more often associated with large‐scale Atlantic cyclones and occur throughout almost the entire year, with the highest precipitation over the mountains. Abstract : About 5–6 times a year, Corsica is affected by events with more than 100 mm of precipitation within 24 h. From surface observations and the ECMWF ERA‐Interim reanalysis, a climatology for such events from 1985 to 2015 is obtained and quantitative methods are used to separate 173 events into three groups, which show distinct seasonal cycles and precipitation distributions with 55% of events occurring from October to December and the eastern half of the island being most affected.